2016
DOI: 10.1186/s12871-016-0270-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for chronic pain following cesarean section: a prospective study

Abstract: BackgroundChronic post-surgical pain (CPSP) remains a major clinical problem which may be associated with impaired activities of daily life and decreased health-related quality of life. Although cesarean section is one of the most commonly performed operations, chronic pain after cesarean delivery has not been well-studied. The purpose of this prospective study was to assess the incidence and risk factors of chronic pain at 3, 6 and 12 months after cesarean delivery.MethodsWe prospectively investigated preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
74
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 36 publications
3
74
0
7
Order By: Relevance
“…In most studies, the incidence of CPSP after cesarean section rarely exceeds 18% at the sixth month [4][5][6][7][8][9]. In a study by Jin et al [17], only 18.3% and 11.3% of patients experienced CPSP three and six months after cesarean section, respectively. The authors of this paper used the Brief Pain Inventory for CPSP evaluation.…”
Section: Discussionmentioning
confidence: 96%
“…In most studies, the incidence of CPSP after cesarean section rarely exceeds 18% at the sixth month [4][5][6][7][8][9]. In a study by Jin et al [17], only 18.3% and 11.3% of patients experienced CPSP three and six months after cesarean section, respectively. The authors of this paper used the Brief Pain Inventory for CPSP evaluation.…”
Section: Discussionmentioning
confidence: 96%
“…months to years to end of life) pain. The intensity and duration of pain in recovery is an important indicator of the likelihood of chronic pain development in humans (Althaus et al, 2018;Boerboom et al, 2018;de Brito, Omanis, Ashmawi, & Torres, 2012;Jin et al, 2016;Rashiq & Dick, 2014;Voscopoulos & Lema, 2010). The fact that human patients with local anaesthetic drugs included in the analgesic protocols were less likely to develop both postoperative and chronic pain is a very compelling reason to utilize local/regional blockade (Boerboom et al, 2018;de Brito et al, 2012;Rashiq & Dick, 2014).…”
mentioning
confidence: 99%
“…In the present study, we found the frequency of chronic pain in the minimum three-month period after the C/S to be 16.4%. Jin et al (11) demonstrated that chronic pain was observed as 18.3%, 11.3% and 6.8% in three, six and 12 months after caesarean section. In another study conducted by Nikolajsen et al (12), which included 220 C/S patients, reported the frequency of chronic pain after C/S to be 18.6% in the first three months, which dropped down to 12.3% ten months later.…”
Section: Discussionmentioning
confidence: 98%